Injectable Biological Treatments for Osteoarthritis of the Knee. Issue 4 (2017) - Weinberg, Maxwell E.; Kaplan, Daniel James; Pham, Hien; Goodwin, David; Dold, Andrew; Chiu, Ernest; Jazrawi, Laith M.
Abstract : The increasing prevalence of knee osteoarthritis in an aging and active population necessitates the development of therapies designed to relieve symptoms, to delay the need for total joint replacement, and to potentially stimulate chondrocyte growth. Growth factor therapies such as platelet-rich plasma have been studied extensively for knee osteoarthritis, with the recent publication of clinical studies. Although the majority of studies conclude that platelet-rich plasma has the potential to provide symptomatic relief on a short-term basis, to our knowledge, long-term data are lacking. Growing interest in stem cell therapy for knee osteoarthritis has led to various studies utilizing mesenchymal stem cells from adipose, bone marrow, or peripheral blood sources. Although studies have shown excellent early clinical results, the ability to improve collection rates of mesenchymal stem cells and methods to direct mesenchymal stem cell differentiation to chondrocytes and to promote chondrogenesis remains a focus for future research. There are still many questions about platelet-rich plasma and its effectiveness for knee osteoarthritis. Differences in preparation technique make effective evaluation and comparison difficult. Bone marrow mesenchymal stem cells currently remain the only stem cell product that appears to be approved by the U.S. Food and Drug Administration (FDA) without any potential questions about use. Further clinical studies are still necessary to fully understand their role.